(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2017)
The whole day had passed but Prof. Sneha, former Director, PUJA College, finds her passion to become an administrator in perplexion. After she had received a phone call from Mr. Navraj, Secretary, Managing Committee, PUJA College at 10a.m., she’s finding her head spinning and splitting. Mr. Navraj had called her to offer once again the post of Director but this time with a higher salary package and other perquisites that she wanted. She’s wondering as to why he’s offering her so much now and not at that time when she used to request about all this couple of months ago. She has also not forgotten the rough tides that she had to face during her stint in PUJA college. She’s in dilemma as to whether she should re-join the college or not.